The Late Positive Potential as a Reliable Neural Marker of Cognitive Reappraisal in Children and Youth: A Brief Review of the Research Literature - Kennedy, Heather; Montreuil, Tina C. (Frontiers in Psychology, 2021)
The mental health of young people is a growing public health concern. With socio-emotional difficulties in youth often resulting in psychiatric disorders later in life, it is essential to support healthy social and emotional development. Using a comprehensive definition of mental health, emotion regulation (ER) plays a critical role and, as such, it becomes imperative to better understand how children effectively manage their emotions from an early age. Determining effective use relies on adequate measurements. However, typical methods of data collection of ER in children present consistent flaws (e.g., lacking generalizability). This review addresses research findings considering the suitability of the late positive potential as measured through electroencephalogram as a neural indicator of ER in youth. There is growing evidence, as reported in studies contained within this review, that indicates that the late positive potential may be a useful neural indicator of children’s cognitive reappraisal abilities. Results generally suggest that late positive potential amplitudes are sensitive to directed reappraisal in children. However, given the small research base, questions remain regarding developmental trends, methodology, interindividual variability, reappraisal of various stimuli, and how the late positive potential may relate to more traditional measures of ER. Directions for future research are provided which are expected to address these unanswered questions and fill gaps in research. Taken together, the findings reviewed indicate that the late positive potential is generally sensitive to directed cognitive reappraisal in children and there is promise of establishing this neural marker as an indicator of ER.